Interferon regulatory factor 4 plays a pivotal role in the development of aGVHD-associated colitis - Jochen T. Frueh; Julia Campe; Daniele Yumi Sunaga-Franze; Nikita A. Verheyden; Sakhila Ghimire; Elisabeth Meedt; Denise Haslinger; Sabine Harenkamp; Daniel Staudenraus; Sascha Sauer; Andreas Kreft; Ralf Schubert; et al. (OncoImmunology, 2024)
Interferon regulatory factor 4 (IRF4) is a master transcription factor that regulates T helper cell (Th) differentiation. It interacts with the Basic leucine zipper transcription factor, ATF-like (BATF), depletion of which in CD4+ T cells abrogates acute graft-versus-host disease (aGVHD)-induced colitis. Here, we investigated the immune-regulatory role of Irf4 in a mouse model of MHC-mismatched bone marrow transplantation. We found that recipients of allogenic Irf4-/- CD4+ T cells developed less GVHD-related symptoms. Transcriptome analysis of re-isolated donor Irf4-/- CD4+ T helper (Th) cells, revealed gene expression profiles consistent with loss of effector T helper cell signatures and enrichment of a regulatory T cell (Treg) gene expression signature. In line with these findings, we observed a high expression of the transcription factor BTB and CNC homolog 2; (BACH2) in Irf4-/- T cells, which is associated with the formation of Treg cells and suppression of Th subset differentiation. We also found an association between BACH2 expression and Treg differentiation in patients with intestinal GVHD. Finally, our results indicate that IRF4 and BACH2 act as counterparts in Th cell polarization and immune homeostasis during GVHD. In conclusion, targeting the BACH2/IRF4-axis could help to develop novel therapeutic approaches against GVHD.